DEMOKRATISASI DESA SEBAGAI LANGKAH MENUJU PEMERINTAHAN DESA YANG DEMOKRATIS - Lailiyah, Kusroh; Maulani, Wihda (Bapelitbang Kabupaten Batang, 2023)
This research aims to determine the implementation of the village democratization system as a step towards democratic village governance. This research uses a qualitative approach through descriptive analysis methods based on literature studies obtained which are then used as analysis material. The results of this research show that village democratization is very important to implement. This is because the practices of authoritarianism and domination are still widely carried out by village elites. There are three steps that can be taken in order to create village democratization. These three steps are controlling the implementation of village democratic procedures and mechanisms, monitoring the level of democratic principles in the implementation of democratic mechanisms, and developing a democratic culture in daily village life and village activities. Apart from that, village democratization can be realized with a village government system that upholds democratic principles and prioritizes control and supervision by the community as the holder of the highest sovereignty. Keywords: Village Democratization, Village Government, Democracy